A Review: Durability of Fired Clay Brick Masonry Wall due to Salt Attack - Abu Bakar, B.H.; Wan Ibrahim, M.H.; Megat Johari, M.A. (International Journal of Integrated Engineering, 2009)
This paper offers a review on durability of fired clay brick masonry wall due to salt attack. Durability of brick normally affected when an external masonry walls are exposed to aggressive environment. Masonry structures, when subjected to salt attack or exposed to aggressive environment during their service life may suffer degradation due to the formation of crystallization pressure as a result of the evaporation of soluble salt in clay masonry structures. The crystallization pressures produce normally higher than tensile stress of clay brick and sufficient to damage the masonry structures. The mechanism of salt attack must be prevented and addressed thoroughly in order to maintain the integrity and service life of masonry wall. Therefore, the summary of durability, factors, mechanism and main sources of salt attack on fired clay brick masonry walls are discussed.